Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1108/qrfm-07-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Investor communication in equity-based crowdfunding: a qualitative-empirical study

Abstract: Purpose -This study's aim is to investigate the role of investor communication in equity-based crowdfunding. The study explores whether and how investor communication can reduce information asymmetries between investors and new ventures in equity-based crowdfunding, thereby facilitating the crowd's investment decisions. Design/methodology/approach -This paper follows an exploratory qualitative research approach based on semi-structured interviews with 23 market participants in equity-based crowdfunding: 12 inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 106 publications
(219 reference statements)
1
95
0
Order By: Relevance
“…Hornuf and Schwienbacher (2015) find that specific kinds of information, such as updates to investors, significantly drive investment as funders update their preferences in the light of project assessment. Moritz et al (2015) examined investor communication in equity crowdfunding, highlighting that perceived sympathy, openness and trustworthiness in the relationship between venture and investor reduced perceived information asymmetries. They also found that third-party communication influences the decision-making process of crowdfunders.…”
Section: Signalling In Early-stage Finance and Information Cascadesmentioning
confidence: 99%
“…Hornuf and Schwienbacher (2015) find that specific kinds of information, such as updates to investors, significantly drive investment as funders update their preferences in the light of project assessment. Moritz et al (2015) examined investor communication in equity crowdfunding, highlighting that perceived sympathy, openness and trustworthiness in the relationship between venture and investor reduced perceived information asymmetries. They also found that third-party communication influences the decision-making process of crowdfunders.…”
Section: Signalling In Early-stage Finance and Information Cascadesmentioning
confidence: 99%
“…Moritz, Block and Lutz [1] show for equity-based crowdfunding that pseudo-personal communication through presentation videos and visualizations in social media channels appear to be a main aspect to transmit relevant information. Thus, we add the variable Picture, which takes the value 1 for crowdfunding descriptions with illustrations and/or photos and 0 otherwise, and also the variable Video, which takes the value 1 for the use of a promotional video.…”
Section: Variablesmentioning
confidence: 98%
“…Mollick [10] uses data from the Kickstarter platform to examine the effects of network connections and quality signals of the project for the funding decision of the crowd and is indeed able to show the relevance of both factors. Furthermore, Moritz, Block and Lutz [1] use semi-structured interviews of 23 market participants to show that the perceived sympathy and trustworthiness by investors is able to reduce information asymmetries between the entrepreneur and equity investors, and, thus, affect the crowds' funding decision to the benefit of the entrepreneur. In particular, they highlight that pseudo-personal communication by the entrepreneur, e.g.…”
Section: Theoretical Background and Hypotheses Development 21 Crowdfmentioning
confidence: 99%
See 1 more Smart Citation
“…First research papers show that educational degrees (Ahlers et al 2015), network relationships (Ahlers et al 2015;Vismara 2016), quality disclosures through external credentials, update information during the campaign (Block, Hornuf, and Moritz 2018;Moritz, Block, and Lutz 2015) and the provision of financial information (Ahlers et al 2015;Lukkarinen et al 2016) can mitigate such potential informational problems and, consequently, influence funding success positively. In particular, Vismara (2016) and Ahlers et al (2015) demonstrate that the retention of equity is an effective signal to increase later campaign success.…”
Section: Introductionmentioning
confidence: 99%